Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Leverage, Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Nilai Perusahaan: Studi pada Perusahaan Food and Baverage yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Sheila Maria Kaunang; Purnama Siddi; Sari Kurniati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to examine the influence of the independent variables profitability, liquidity, company size, leverage, managerial ownership and institutional ownership and the dependent variable firm value. The object of this research is food and beverage companies listed on the Indonesia Stock Exchange 2019 - 2022. The sampling method used is the purposive sampling technique. This research was conducted on 19 companies and the number of observations was 532 data using a quantitative-descriptive approach. The analytical method used is multiple regression which consists of classic assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test) and hypothesis tests (coefficient of determination test, T test, F test). The results of this research show that profitability and leverage have a positive and significant effect on company value, while liquidity, company size, managerial ownership and institutional ownership have no effect on company value.